Am I a Monkey? : Six Big Questions about Evolution - Ayala, Francisco Jose, 1934- (Book collections on Project MUSE., 2010)
"Despite the ongoing cultural controversy in America, evolution remains a cornerstone of science. In this book, Francisco J. Ayala---an evolutionary biologist, member of the National Academy of Sciences, and winner of the National Medal of Science and the Templeton Prize---cuts to the chase in a daring attempt to address, in nontechnical language" "This to-the-point book answers each of these questions with force. Ayala's occasionally biting essays refuse to lend credence to disingenuous ideas and arguments. He lays out the basic science that underlies evolutionary theory, explains how the process works, and soundly makes the case for why evolution is not a threat to religion." "Brief, incisive, topical, authoritative, Am I a Monkey? will take you a day to read and a lifetime to ponder."--BOOK JACKET.